Coulomb explosion imaging of CH3I and CH2ClI photodissociation dynamics - Allum, Felix; Burt, Michael; Amini, Kasra; Boll, Rebecca; Köckert, Hansjochen; Olshin, Pavel K.; Bari, Sadia; Bomme, Cédric; Brauße, Felix; Cunha de Miranda, Barbara; Düsterer, Stefan; Erk, Benjamin; et al. (My University, 2018)
The photodissociation dynamics of CH3I and CH2ClI at 272 nm were investigated by time-resolved Coulomb explosion imaging, with an intense non-resonant 815 nm probe pulse. Fragment ion momenta over a wide m/z range were recorded simultaneously by coupling a velocity map imaging spectrometer with a pixel imaging mass spectrometry camera. For both molecules, delay-dependent pump-probe features were assigned to ultraviolet-induced carbon-iodine bond cleavage followed by Coulomb explosion. Multi-mass imaging also allowed the sequential cleavage of both carbon-halogen bonds in CH2ClI to be investigated. Furthermore, delay-dependent relative fragment momenta of a pair of ions were directly determined using recoil-frame covariance analysis. These results are complementary to conventional velocity map imaging experiments and demonstrate the application of time-resolved Coulomb explosion imaging to photoinduced real-time molecular motion.